2007
DOI: 10.18251/ijme.v9i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a True Pluralistic Dialogue: A Particularistic Multicultural Teacher Accreditation Program for Israeli Bedouins

Abstract: This paper reports on a preliminary assessment of a unique teacher accreditation program that was established in a college in southern Israel in an attempt to improve the Arab Bedouins' educational system and to promote a true dialogue between Bedouins and Jewish students on the basis of a particularistic multicultural approach. Data was collected and analyzed by employing a combination of several qualitative methods including content analysis of program-related documents and interviews with students and facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…From the research results above, it can be concluded that the background of MEM is based on six foundations, namely philosophical, juridical, historical, sociological, geographic, and futuristic foundations [34]. For the schools that are the subject of research, all of them have challenges.…”
Section: Discussionmentioning
confidence: 99%
“…From the research results above, it can be concluded that the background of MEM is based on six foundations, namely philosophical, juridical, historical, sociological, geographic, and futuristic foundations [34]. For the schools that are the subject of research, all of them have challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavioral implications have direct consequences to multicultural education as one of its goals is the advancement of positive intergroup meetings. Whether the particularistic or pluralistic educational approach is embraced (Reingold, 2007), the intergroup contact could largely depend on the type of CE participants have. For example, having two groups of mainly Monocultural individuals may prove hazardous to the success of such an encounter since the epistemic gap will be too far to bridge.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, “vestigial multiculturalism”, permanently preserves some of the minority group’s marginal cultural dimensions (Sever, 2001). The pluralist multicultural ideology does not ask temporarily communities to relinquish their unique cultures; rather, it seeks to conduct a dialog on the cultural boundaries between the various groups that preserve their particularistic cultures, without any implicit hierarchies or attempts at cultural colonialism (Reingold, 2007).…”
Section: Theoretical Backgroundmentioning
confidence: 99%